DEVELOPING ECOLOGY LEARNING OBJECT MATERIALS FOR IMPROVING STUDENTS CRITICAL THINKING SKILLS OF MADRASAH ALIYAH - H. Muhammad Zaini; Retno Jumirah (University of Muhammadiyah Malang, 2016)
Research and development is aimed to produce a learning tool topic ecology to students' critical thinking skills madrasah aliyah valid, practical, and effective. The study uses a model Mafumiko development. The research subjects Biology class X, X MIA 3 MAN 2 Model Banjarmasin include individual testing, small group test and field test. Data were collected through tests and observation. Analysis of descriptive data. The results showed the learning device has been valid for at least based on 1) the validation study results also experts with at least valid, and 2) validation team classified panel invalid. Learning devices including practically covers 1) keterlaksanaan RPP obtained very good results, 2) students showed a positive response to strongly agree 70% and agreed by 30%, and 3) teachers showed a positive response to learning learning devices classified as effective by 1) mastery of learning outcomes has reached 80 ± 2.67 of KKM students converted the letter B -, 2) assessment process was very good category, 3) assessment psychomotor excellent category, 4) spiritual assessment category very well, 5) ratings categories very good character, 6) better assessment of students' critical thinking, 7) ratings of social skills to work together and contribute ideas with excellent and good categories, 8) assessment of student activity in both categories, and 9) assessment of teacher activity with very good category.